Problematika Yuridis Vonis Bebas dalam Penegakan Hukum Tindak Pidana Korupsi - Baktiyasa, I (Indonesian Journal Publisher, 2026)
This study is motivated by the phenomenon of increasing acquittal verdicts, which has triggered public skepticism regarding the effectiveness of law enforcement and legal certainty for state finances. This research aims to analyze two primary issues: 1) What is the efficacy and contribution of police investigators in conducting the series of investigation processes for corruption crimes? 2) What is the regulatory construction regarding acquittal verdicts and its juridical implications for the limits of the prosecutor's authority when viewed from the perspective of criminal procedural law applicable in Indonesia? The research method applied relies on a normative legal approach. The study was conducted through an in-depth review of library materials, including statutory regulations, Supreme Court jurisprudence, and various academic literatures relevant to the issues under investigation. This approach relies on library research. The results indicate that the success of law enforcement depends heavily on the quality of material evidence at the investigation stage and the prosecutor's ability to challenge the rigidity of Article 244 of the Criminal Procedure Code (KUHAP) through jurisprudence. The consistency of judicial considerations and the integrity of law enforcement officials are crucial instruments for minimizing the loopholes of acquittal verdicts to protect fiscal interests and the nation's legal dignity.